Efficacy and safety of pembrolizumab versus sintilimab treatment in patients with advanced squamous lung cancer: A real-world study in China - Yang, Wenyu; Li, Tao; Bai, Yibing; Long, Yaping; Gao, Ming; Wang, Ting; Jing, Fangfang; Zhang, Fan; Tao, Haitao; Ma, Junxun; Wang, Lijie; Hu, Yi (Frontiers in Oncology, 2023)
Importance Both pembrolizumab and sintilimab have been approved by the Chinese State Drug Administration (NMPA) for the first-line treatment of patients with advanced squamous lung cancer. The differences of the two drugs in efficacy and safety are unclear. Objectives To compare the real-world efficacy and safety of first-line treatments in patients with advanced squamous lung cancer. Materials and methods This was a retrospective review of patients with advanced squamous carcinoma who received sintilimab or pembrolizumab in combination with chemotherapy as first-line therapy between June 2018 and April 2022 in the Chinese PLA Hospital. The primary objective was to compare the objective response rate (ORR), progression-free survival (PFS), and overall survival (OS) between the two groups. Secondary objectives were to compare the disease control rate (DCR) and to analyze adverse events (AEs) between the two groups. Results A total of 164 patients were enrolled, including 63 patients (38.4%) in the sintilimab-combined chemotherapy group and 101 patients (61.6%) in the pembrolizumab-combined chemotherapy group. The ORR was 65.10% in the sintilimab group and 61.40% in the pembrolizumab group (P=0.634). The DCR was 92.10% and 92.10% in the sintilimab and pembrolizumab groups, respectively (P=0.991). The median PFS was 22.2 months for patients treated with sintilimab group compared with 16.5 months for patients treated with pembrolizumab group[hazard ratio (HR) = 0.743; 95% confidence interval (CI): 0.479-1.152; P = 0.599]. Patients treated with pembrolizumab did not achieve a median OS, and patients treated with sintilimab had a median OS of 30.7 months. In the sintilimab group, the incidence of all treatment-related adverse events (TRAEs) was 92.1% (58/63), and the incidence of grade 3-4 TRAEs of 42.9% (27/63). In the pembrolizumab group, the incidence of all TRAEs was 90.1% (91/101), and the incidence of grade 3-4 TRAEs was 37.6% (38/101). Conclusion In the clinical treatment of Chinese patients with advanced squamous lung cancer, first-line treatment with sintilimab in combination with chemotherapy provided similar efficacy to pembrolizumab in combination with chemotherapy, and the treatment-related adverse effect profiles were comparable between the two groups, including similar rates of grade 3-4 and all adverse events.